Trypanocidal drug resistance in West Africa - D'Ieteren, G.D.M.; Coulibaly, L.; Atse, P.A.; Hecker, P.A.; Krebs, H.A.; Rowlands, G.J.; Leak, S.G.A.; Nagda, S.M. (European Union, 2000)
In this study, the efficacies of three trypanocidal drugs, diminazene aceturate, isometamidium chloride and homidium bromide, were evaluated in four representative areas of Cote d'Ivoire with different production systems, degree of integration of different trypanosomosis control approaches and delivery of veterinary inputs.